2017
DOI: 10.1007/s00402-017-2826-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of concurrent procedures during high tibial osteotomy for medial compartment osteoarthritis: a systematic review and meta-analysis

Abstract: Our analysis support that concurrent procedures during HTO for medial compartment OA have little beneficial effect regarding clinical and radiological outcomes. However, they might have some beneficial effects in terms of arthroscopic, histologic, and MRI findings even though the quality of healed cartilage is not good as that of original cartilage. Therefore, until now, concurrent procedures for medial compartment OA have been considered optional. Nevertheless, no conclusions can be drawn for younger patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…These treatments have been applied in regular care for a long time and have been evaluated extensively. [4][5][6][7] Unicompartmental knee arthroplasty is an option in unilateral OA as well. A newer joint-preserving treatment for knee OA is knee joint distraction (KJD).…”
Section: Introductionmentioning
confidence: 99%
“…These treatments have been applied in regular care for a long time and have been evaluated extensively. [4][5][6][7] Unicompartmental knee arthroplasty is an option in unilateral OA as well. A newer joint-preserving treatment for knee OA is knee joint distraction (KJD).…”
Section: Introductionmentioning
confidence: 99%
“…The pooled results of our analysis indicated that the medium-and long-term clinical outcomes were not related to the arthroscopic and histologic outcomes, this question was also mentioned by several studies, 17,33,34 the reason maybe as follows: First, the mechanical properties and durability of neoformative cartilage are different from healthy hyaline cartilage. Second, it is probable that growth of repair cartilage after marrow stimulation progresses slowly and it will take more than 5 years.…”
Section: Discussionmentioning
confidence: 56%
“…10 To improve the longterm outcomes many cartilage repair procedures appeared, such as microfractures (MFs) and autologous chondrocyte implantation (ACI). 11 Some researcher reported that cartilage repair procedures had a significant effect on cartilage regeneration and improved clinical outcomes obviously, [12][13][14][15] while some authors reported that the procedures have little beneficial effect on cartilage regeneration or clinical outcomes, 16,17 even had an opposite effect. 10 Therefore, whether we should perform cartilage repair procedures during HTO for osteoarthritic knee is controversial.…”
mentioning
confidence: 99%
“…However, osteoarthritis progression may occur with a long term follow-up, and requiring conversion to TKA [30][31][32]. In addition, a systematic review and meta-analysis [33] found the HTO with concurrent cartilage procedures such as marrow stimulation procedure, mesenchymal stem cell transplantation, and injection were performed, but the concurrent procedures would produce little beneficial effect regarding clinical and radiological outcomes compared with HTO alone. In the included studies, the mean time interval between HTO and TKA ranged from 58 to 150 months (Table 1), which suggests that HTO is still a successful and reliable treatment method for unicompartmental knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%